Development of a Reliable Surgical Quality Assurance System for 2-stage Esophagectomy in Randomized Controlled Trials. Issue 1 (January 2022) - Harris, Alexander; Butterworth, James; Boshier, Piers R.; MacKenzie, Hugh; Tokunaga, Masanori; Sunagawa, Hideki; Mavroveli, Stella; Ni, Melody; Mikhail, Sameh; Yeh, Chi-Chuan; Blencowe, Natalie S.; Avery, Kerry N. L.; et al.
Abstract : Objective: The aim was to develop a reliable surgical quality assurance system for 2-stage esophagectomy. This development was conducted during the pilot phase of the multicenter ROMIO trial, collaborating with international experts. Summary of Background Data: There is evidence that the quality of surgical performance in randomized controlled trials influences clinical outcomes, quality of lymphadenectomy and loco-regional recurrence. Methods: Standardization of 2-stage esophagectomy was based on structured observations, semi-structured interviews, hierarchical task analysis, and a Delphi consensus process. This standardization provided the structure for the operation manual and video and photographic assessment tools. Reliability was examined using generalizability theory. Results: Hierarchical task analysis for 2-stage esophagectomy comprised fifty-four steps. Consensus (75%) agreement was reached on thirty-nine steps, whereas fifteen steps had a majority decision. An operation manual and record were created. A thirty five-item video assessment tool was developed that assessed the process (safety and efficiency) and quality of the end product (anatomy exposed and lymphadenectomy performed) of the operation. The quality of the end product section was used as a twenty seven-item photographic assessment tool. Thirty-one videos and fifty-three photographic series were submitted from the ROMIO pilot phase for assessment. The overall G-coefficient for the video assessment tool was 0.744, and for the photographic assessment tool was 0.700. Conclusions: A reliable surgical quality assurance system for 2-stage esophagectomy has been developed for surgical oncology randomized controlled trials. Ethical approval: 11/NW/0895 and confirmed locally as appropriate, 12/SW/0161, 16/SW/0098. Trial registration number: ISRCTN59036820, ISRCTN10386621. Abstract : Supplemental Digital Content is available in the text